2010
DOI: 10.1103/physrevlett.105.246601
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoconductance Oscillations and Evidence for Fractional Quantum Hall States in Suspended Bilayer and Trilayer Graphene

Abstract: We report pronounced magnetoconductance oscillations observed on suspended bilayer and trilayer graphene devices with mobilities up to 270,000 cm²/V s. For bilayer devices, we observe conductance minima at all integer filling factors ν between 0 and -8, as well as a small plateau at ν=1/3. For trilayer devices, we observe features at ν=-1, -2, -3, and -4, and at ν∼0.5 that persist to 4.5 K at B=8 T. All of these features persist for all accessible values of Vg and B, and could suggest the onset of symmetry bre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 34 publications
2
89
1
Order By: Relevance
“…Depending on sample quality, electron-electron interactions also contribute to symmetry breaking and Landau level splitting, [67][68][69][70][71][72][73][74][75][76][77][78][79] as does interlayer asymmetry due to the presence of an external gate or doping. 28,31,42,45,[80][81][82] Nevertheless, an experimental observation of features related to next-nearest layer couplings should be possible in high-mobility samples including suspended graphene 69,[83][84][85][86] or graphene on a boron nitride substrate. 66,72,73,87 In fact, Landau level crossings in trilayer graphene were recently observed, 66 and they allowed the determination of Slonczewski-Weiss-McClure parameter values in remarkably close agreement with those of bulk graphite.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on sample quality, electron-electron interactions also contribute to symmetry breaking and Landau level splitting, [67][68][69][70][71][72][73][74][75][76][77][78][79] as does interlayer asymmetry due to the presence of an external gate or doping. 28,31,42,45,[80][81][82] Nevertheless, an experimental observation of features related to next-nearest layer couplings should be possible in high-mobility samples including suspended graphene 69,[83][84][85][86] or graphene on a boron nitride substrate. 66,72,73,87 In fact, Landau level crossings in trilayer graphene were recently observed, 66 and they allowed the determination of Slonczewski-Weiss-McClure parameter values in remarkably close agreement with those of bulk graphite.…”
Section: Discussionmentioning
confidence: 99%
“…The order at which the degeneracy is broken reflects the underlying competing symmetries. Prior works have reported resolution of several symmetry-broken QH states [38][39][40] , albeit only in single-gated samples where the interlayer potential U⊥ and charge density n are not independently controlled. In this Letter, by using transport measurements on high mobility dual-gated r-TLG devices, we explore symmetry-broken LLs via careful control of U⊥, B and n. All integer plateaus of the zeroth LL in the hole-doped regime are resolved in high B.…”
mentioning
confidence: 99%
“…11 Further broken symmetry states have been observed [12][13][14][15][16] in the central Landau band at ν = 0, ±1, ±2 and ±3, and by careful tilted-field measurements it has been shown that they arise predominantly from many-body effects, i.e., from quantum Hall ferromagnetism (QHF). 17 Quantum Hall states with broken symmetry have also been found in the n = −2 Landau level 18 , and there is also some evidence for a fractional quantum Hall plateau.…”
Section: Introductionmentioning
confidence: 98%